2020
DOI: 10.1016/j.isci.2020.101755
|View full text |Cite
|
Sign up to set email alerts
|

CARM1 Regulates AMPK Signaling in Skeletal Muscle

Abstract: Summary Coactivator-associated arginine methyltransferase 1 (CARM1) is an emerging mediator of skeletal muscle plasticity. We employed genetic, physiologic, and pharmacologic approaches to determine whether CARM1 regulates the master neuromuscular phenotypic modifier AMP-activated protein kinase (AMPK). CARM1 skeletal muscle-specific knockout (mKO) mice displayed reduced muscle mass and dysregulated autophagic and atrophic processes downstream of AMPK. We observed altered interactions between CARM1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(90 citation statements)
references
References 58 publications
17
72
1
Order By: Relevance
“…FoxO3 also aids in the control of mitophagy through Bcl2 and adenovirus E1b 19-kDa-interacting protein 3 (Bnip3) and Bnip3-like (Nix) gene expression [ 31 ]. The importance of FoxO3 in muscle was shown in a series of seminal studies, whereby constitutively active FoxO3 promotes atrophy [ 28 , 30 , 31 ], whereas blunted FoxO3 activity prevents stimulus-induced atrophy of muscle fibers through perturbations in both proteasomal and autophagic pathways [ 28 , 32 , 33 , 34 , 35 , 36 ]. Tfeb and Tfe3 homodimerize and/or heterodimerize and interact with E-box and M-Box elements in promoters [ 37 , 38 , 39 ], and they regulate the expression of both lysosome and autophagy-related genes via their ability to activate the coordinated lysosome enhancement and regulation (CLEAR) network of genes [ 38 , 40 , 41 , 42 , 43 ].…”
Section: Regulation Of Autophagy In Musclementioning
confidence: 99%
See 1 more Smart Citation
“…FoxO3 also aids in the control of mitophagy through Bcl2 and adenovirus E1b 19-kDa-interacting protein 3 (Bnip3) and Bnip3-like (Nix) gene expression [ 31 ]. The importance of FoxO3 in muscle was shown in a series of seminal studies, whereby constitutively active FoxO3 promotes atrophy [ 28 , 30 , 31 ], whereas blunted FoxO3 activity prevents stimulus-induced atrophy of muscle fibers through perturbations in both proteasomal and autophagic pathways [ 28 , 32 , 33 , 34 , 35 , 36 ]. Tfeb and Tfe3 homodimerize and/or heterodimerize and interact with E-box and M-Box elements in promoters [ 37 , 38 , 39 ], and they regulate the expression of both lysosome and autophagy-related genes via their ability to activate the coordinated lysosome enhancement and regulation (CLEAR) network of genes [ 38 , 40 , 41 , 42 , 43 ].…”
Section: Regulation Of Autophagy In Musclementioning
confidence: 99%
“…This may be explained, in part, by the relatively inconsistent measures of AKT activity that exist in the literature [ 104 , 106 , 107 , 108 , 109 ]. Further, deacetylation of FoxO3 by histone deacetylase 1 (HDAC1) [ 73 , 110 , 111 ] and co-activation by CARM1 [ 32 , 33 ] enhance FoxO3 function, and are implicated in disuse/denervation atrophy. Both mechanisms have not been investigated in aged muscle.…”
Section: Regulation Of Autophagy In Musclementioning
confidence: 99%
“…CARM1 is also emerging as an important regulator of skeletal muscle biology, a dynamic tissue accounting for 30–40% of body mass that is essential for metabolism, respiration, and mobility [ 12 ]. Indeed, we [ [13] , [14] , [15] , [16] , [17] , [18] , [19] ] and others [ [20] , [21] , [22] , [23] , [24] , [25] ] have shown that CARM1 expression and activity are altered during conditions of muscle plasticity and that the methyltransferase is required for myogenesis, glucose metabolism, and the maintenance and remodelling of muscle mass. In particular, recent work has highlighted CARM1-mediated autophagic and atrophic signalling in skeletal muscle [ 15 , 19 , [24] , [25] , [26] ], revealing a mechanism by which CARM1 influences AMP-activated protein kinase (AMPK) and its downstream network to affect muscle mass.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that CARM1 can regulate the activation of AMPK in skeletal muscle during denervation-induced plasticity. CARM1 interacts with AMPK and causes the methylation of AMPK, resulting in AMPK activation [ 61 ]. This result is consistent with the increased AMPK activation in CARM1-overexpressing cells in our study.…”
Section: Discussionmentioning
confidence: 99%